Personal Identity After an Autism Diagnosis: Relationships With Self-Esteem, Mental Wellbeing, and Diagnostic Timing - Corden, Kirsten; Brewer, Rebecca; Cage, Eilidh (Frontiers in Psychology, 2021)
Adults are increasingly seeking autism diagnoses, although less is known about their experiences of diagnosis and personal identity (i.e., autism as part of ‘me’), and how this relates to self-esteem and wellbeing. One-hundred and fifty-one autistic adults completed an online survey including measures of self-esteem, psychological wellbeing and autistic personal identity, which considered whether participants took pride in or were dissatisfied with being autistic. Fifty-four participants answered a qualitative question about the impact of receiving an autism diagnosis on their sense of self. Regression analyses found that greater time elapsed since diagnosis related to less dissatisfaction with autistic personal identity. We also found that more dissatisfaction with autistic personal identity predicted lower self-esteem, and more autism pride predicted higher self-esteem. Content analysis of participants’ experiences supported the quantitative findings and were suggestive of an emotive post-diagnostic adjustment process. Future research should aim to identify ways to promote the development of a positive autistic personal identity post-diagnosis in adulthood.